Effect Of Bhringraj (Eclipta Alba) Herb On In Vitro Fermentation Characteristics Of Bajra Straw And Bajra Straw-Based Complete Feed (Applied Biological Research, 2011)
An experiment was conducted to assess the effect of Bhringraj (Eclipta alba)  herb supplementation to bajra straw @ 0, 1, 2, 3 and 4% kg-1 dry matter  substrate on degradability of dry matter (DM), organic matter (OM) and  neutral detergent fibre (NDF) and total gas production (TGP) using goat rumen  liquor. Significant improvement in nutrient degradability of DM, OM and NDF  in bajra straw and TGP production was observed due to Bhringraj  supplementation with maximum values at 3% kg-1 DM. Another in vitro trial  was performed to evaluate the effect of 3% Bhringraj kg-1 DM on rumen  fermentation characteristics in complete feed having bajra straw and  concentrate mixture in 60:40 ratio. The treatment significantly improved  nutrient degradability (DM, OM and NDF), TGP, total rumen nitrogen and  TVFA in comparison to control. Addition of Bhringraj in complete feed did not  alter rumen pH, however there was significant decrease in rumen ammonia nitrogen in herb supplemented complete feed.
Keywords: Bajra straw; complete feed; Eclipta alba; gas production; in vitro degradability; rumen fermentation